Coccolithophore Assemblage Dynamics and Emiliania huxleyi Morphological Patterns During Three Sampling Campaigns Between 2017 and 2019 in the South Aegean Sea (Greece, NE Mediterranean) - Patrick James F. Penales; Elisavet Skampa; Margarita D. Dimiza; Constantine Parinos; Dimitris Velaoras; Alexandra Pavlidou; Elisa Malinverno; Alexandra Gogou; Maria V. Triantaphyllou (Geosciences)
This study presents the living coccolithophore communities and the morphological variability of Emiliania huxleyi in the South Aegean Sea from three sampling regions during winter-early spring (March 2017, March 2019) and summer (August 2019). Emphasis is given to March 2017 to monitor the variations in coccolithophore assemblages after an exceptionally cold event in December 2016, which resulted in newly produced dense waters that ventilated the Aegean deep basins. The assemblages displayed distinct seasonality with the predominance of E. huxleyi and Syracosphaera molischii during winter-early spring, associated with the water column mixing. By contrast, summer assemblages were featured by holococcolithophores and typical taxa of warm, oligotrophic upper waters. It seems that the phytoplanktonic succession as well as the nutrient supply to the upper euphotic layers were affected by the water column perturbation during the extreme winter of 2016–2017, which led to strong convective mixing and dense water formation. The decreased coccosphere densities during March 2017, accompanied by the notable presence of diatoms, were most probably associated with a prolonged diatom bloom, causing delay in the development of the coccolithophore community and resulting in a nitrogen-limited setting. Emiliania huxleyi morphometry showed the characteristic seasonal calcification trend of the Aegean, with the dominance of smaller coccoliths in the summer and increased coccolith length and width during the cold season. The intense cold conditions and wind-induced mixing during the winter of 2016–2017 possibly increased the absorption of atmospheric CO2 in surface waters, causing increased acidity and the subsequent presence of etched/undercalcified E. huxleyi coccoliths and other taxa, most probably implying in situ calcite dissolution.